2006
DOI: 10.1529/biophysj.105.067595
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Headgroup Discrimination by Antimicrobial Peptide LL-37: Insight into Mechanism of Action

Abstract: Interaction of the human antimicrobial peptide LL-37 with lipid monolayers has been investigated by a range of complementary techniques including pressure-area isotherms, insertion assay, epifluorescence microscopy, and synchrotron x-ray scattering, to analyze its mechanism of action. Lipid monolayers were formed at the air-liquid interface to mimic the surface of the bacterial cell wall and the outer leaflet of erythrocyte cell membrane by using phosphatidylglycerol (DPPG), phosphatidylcholine (DPPC), and pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
168
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 150 publications
(208 citation statements)
references
References 71 publications
(113 reference statements)
38
168
2
Order By: Relevance
“…7, circles) fit well with a two-slab model, yielding a hydrocarbon tail density ( t / s ) of 0.99 and a hydrocarbon tail slab thickness (L 1 ) of 17.9 Å as well as a head-group electron density ( h / s ) of 1.54 and head-group slab thickness (L 2 ) of 5.7 Å. These data are in good agreement with previous DPPG monolayer x-ray work (51). The XR profile changed dramatically after 1 was introduced (Fig.…”
Section: X-ray Reflectivity Studies Of Ampetoid Orientation In Lipid supporting
confidence: 87%
See 1 more Smart Citation
“…7, circles) fit well with a two-slab model, yielding a hydrocarbon tail density ( t / s ) of 0.99 and a hydrocarbon tail slab thickness (L 1 ) of 17.9 Å as well as a head-group electron density ( h / s ) of 1.54 and head-group slab thickness (L 2 ) of 5.7 Å. These data are in good agreement with previous DPPG monolayer x-ray work (51). The XR profile changed dramatically after 1 was introduced (Fig.…”
Section: X-ray Reflectivity Studies Of Ampetoid Orientation In Lipid supporting
confidence: 87%
“…The orientation of 1 at an angle of Ϸ56°to the interface normal suggests that 1 does not operate through a barrel-stave mechanism, because that would require a transmembrane configuration (5). Although it cannot be concluded that 1 exhibits identical mechanistic behavior to natural, ␣-helical antimicrobial peptides, these x-ray results demonstrate ampetoid-lipid interactions consistent with those seen for AMPs such as pexiganan (53) and LL-37 (51).…”
Section: Discussionmentioning
confidence: 54%
“…Further, it is very reasonable that no water molecules exist in the tailgroup, because the tailgroup are composed of two linear aliphatic chains, which are highly hydrophobic. In that case, the expanded region will not be filled efficiently with water molecules, but remained empty [23][24][25]. Consequently the electron densities of head and tail layer will be reduced by the peptide insertion (Figure 3(c)).…”
Section: X-ray Reflectivity Of Tdp On Model Phospholipid Monolayersmentioning
confidence: 99%
“…Our current understanding of how this AMP attacks bacteria has been shaped by bulk assays (11,12), model membrane assays (13)(14)(15)(16)(17)(18), and assumptions based on studies of other AMPs. Minimum inhibitory concentration (MIC) assays, which determine the lowest concentration of peptide that inhibits bacterial growth, show that LL-37 is effective against a broad spectrum of bacteria that is both Gram-positive and -negative (12).…”
mentioning
confidence: 99%